Strategi Branding Image Madrasah dan Preferensi Orang Tua: Studi Kasus MAN 1 Konawe Selatan - Asih Wulandari; Akib; Syamsuddin (Yayasan Ishlahul Muslimin Konawe Selatan, 2025)
The background of this study is based on the importance of school image in shaping public trust and interest in educational institutions, especially amidst increasingly competitive school competition. In this context, branding image does not only include visual aspects such as logos and slogans, but also reflects the values, culture, and quality of education offered. This study aims to describe the branding image strategy and its impact on increasing parental preference of students at MAN 1 Konawe Selatan. This study utilised a qualitative approach with a case study design. Data was collected through field observations, in-depth interviews, and documentation. Data credibility was tested using Miles and Huberman's theory. The results show that the branding image strategy at MAN 1 Konawe Selatan is carried out through three main approaches, namely: brand positioning (positioning the school's image as a superior and religious madrasah), brand identity (building an institutional identity through the vision and mission, logo, tagline, and social media), and brand personality (instilling religious, knowledgeable, and Islamic character in the entire academic community). The impact of this strategy has succeeded in forming the image of a madrasah that is religious, superior in science and technology, and has an Islamic personality, thereby increasing parental trust and preference in choosing a school. Parents feel confident in the programs offered and believe that MAN 1 Konawe Selatan is the best place to nurture their children academically and spiritually. This research contributes to the development of Islamic education management strategies, particularly in strengthening madrasah competitiveness through a planned and sustainable branding approach.